2016
DOI: 10.1093/pasj/psw056
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray luminosity function of tidal disruption events: First results from the MAXI extragalactic survey

Abstract: We derive the first hard X-ray luminosity function (XLF) of stellar tidal disruption events (TDEs) by supermassive black holes (SMBHs), which gives an occurrence rate of TDEs per unit volume as a function of peak luminosity and redshift, utilizing an unbiased sample observed by the Monitor of All-sky X-ray Image (MAXI). On the basis of the light curves characterized by a power-law decay with an index of −5/3, a systematic search using the MAXI data in the first 37 months detected four TDEs, all of which have b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…However, it would be beneficial if we could constrain observationally the LF of TDEs, as this would provide us with a way to experimentally constrain the contribution of TDEs to the growth of BHs in the local universe, while providing a useful tool to predict the number of possible events one could detect in future X-ray surveys using instruments such as eROSITA 11 . Recently, Kawamuro et al (2016) made the first attempt to characterise observationally the hard (4-10 keV) X-ray LF of TDEs using a flux limited sample of TDE events detected using 37 months of MAXI data. From their study, they find TDEs do not contribute significantly to the hard X-ray LF of AGN for z < 1.5, and thus their contribution to the BH growth at these redshifts is negligible.…”
Section: Soft X-ray Luminosity Function Of X-ray Tdesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it would be beneficial if we could constrain observationally the LF of TDEs, as this would provide us with a way to experimentally constrain the contribution of TDEs to the growth of BHs in the local universe, while providing a useful tool to predict the number of possible events one could detect in future X-ray surveys using instruments such as eROSITA 11 . Recently, Kawamuro et al (2016) made the first attempt to characterise observationally the hard (4-10 keV) X-ray LF of TDEs using a flux limited sample of TDE events detected using 37 months of MAXI data. From their study, they find TDEs do not contribute significantly to the hard X-ray LF of AGN for z < 1.5, and thus their contribution to the BH growth at these redshifts is negligible.…”
Section: Soft X-ray Luminosity Function Of X-ray Tdesmentioning
confidence: 99%
“…From their study, they find TDEs do not contribute significantly to the hard X-ray LF of AGN for z < 1.5, and thus their contribution to the BH growth at these redshifts is negligible. Unfortunately, due to the limited number of TDEs that emit significantly in the hard X-ray energy band, Kawamuro et al (2016) likely miss a large number of TDE candidates that could be used to derive the X-ray …”
Section: Soft X-ray Luminosity Function Of X-ray Tdesmentioning
confidence: 99%
“…Alternatively, it has previously been shown in the literature that some thermal TDE's also have a non-thermal emission component in the 2-10 keV band, as in the TDE XMMSL1 J0740-85 (Kawamuro et al 2016;Saxton et al 2017). This power-law component is thought to be from the hot corona which Comptonizes the thermal optically thick disk emission.…”
Section: Cygnus A-2 As a Tdementioning
confidence: 99%
“…The source position estimated with the MAXI/GSC turned out to be consistent with that of 2MAXIt J1807+132, which is listed in the MAXI/GSC transient source catalog (Kawamuro et al 2016), based on an X-ray flaring event detected in 2011 May.…”
Section: Introductionmentioning
confidence: 57%
“…Kawamuro et al (2016) concluded that 2MAXIt J1807+132 is unlikely a TDE, because it has exhibited multiple enhancements (though with lower significances, at ∼2σ levels) from 2009 to 2013. Identifying the present source MAXI J1807+132 with 2MAXIt J1807+132, the TDE interpretation becomes even less likely, because the interval of the two strongest flaring events is much shorter than those predicted for TDEs (typically ∼10 4 to ∼10 5 years; e.g., Kawamuro et al 2016). To search for other brightening episodes of MAXI J1807+132 (=2MAXIt J1807+132), we analyzed the entire MAXI/GSC data of this sky region using the ondemand process system 3 .…”
Section: The Nature Of Maxi J807+132mentioning
confidence: 99%